Walt disnep's: bambi (Spotlight, a division of ABDO Minneapolis, Minnesota, 2021)
Hailed as the Prince of the Forest at his birth, wobble-legged Bambi the fawn lives deep in the woodland with his mother. His youth is filled with friends--Thumper, a jovial rabbit who says all the wrong things; Flower, a skunk with an inferiority complex; and Friend Owl, misanthrope of the treetops. As he grows, fun-and-games give way to the hardship of winter and the most terrifying, ever-looming threat to survival--man. When the hunters come, Bambi must learn to be as brave as his father The Great Prince, and lead the other deer to safety